Molecular exchange at the lipid-rhodopsin interface: spin-label electron spin resonance studies of rhodopsin-dimyristoylphosphatidylcholine recombinants. - Ryba, N; Horváth, L; Watts, A; Marsh, D (1987)
The photoreceptor protein rhodopsin has been reconstituted with a single phospholipid species, dimyristoylphosphatidylcholine, at a range of different lipid/protein ratios, and the exchange rate at the lipid-protein interface has been determined from the electron spin resonance spectra of spin-labeled phosphatidylcholine. For recombinants with lipid/protein ratios in the range 41:1 to 102:1 (mol/mol), the electron spin resonance spectra of 1-acyl-2-[14-(4,4-dimethyloxazolidine-N-oxyl)stearoyl]-sn-glycero-3- phosphocholine consist of a fluid component similar to that found in pure lipid bilayers and a motionally restricted component corresponding to lipids whose motion is reduced by interaction with the intramembranous surface of rhodopsin. The relative proportion of the motionally restricted component increases with increasing protein content in the complex. Spectral subtraction with fluid and motionally restricted components (from fluid- and gel-phase lipid, respectively), which best fit the apparent components in the complex, reveals that 22 +/- 2 lipids per 39,000-dalton protein are motionally restricted, independent of lipid/protein ratio and of temperature. Simulation of the two-component spectra with the exchanged-coupled Bloch equations gives values for both the fraction of motionally restricted component and the exchange rate between the two components. Using fixed motionally restricted and fluid component line shapes at a given temperature, it is possible to obtain a consistent description of the lipid/protein ratio dependence of the spectra at each temperature. The number of motionally restricted lipids obtained by simulation, allowing for exchange, is 23 +/- 3 per 39,000-dalton protein, again independent of temperature and of lipid/protein ratio.(ABSTRACT TRUNCATED AT 250 WORDS)